Effectiveness of Jurisprudential Inquiry Learning Model to Improve Student Learning Achievement in Geography Subject at SMAN 2 Bengkulu Utara - Lamtiur Tampubolon; Alexon Alexon (CV. Media Inti Teknologi, 2023)
This study aims to explain (1) How the Jurisprudential Inquiry learning model can be applied to SMA N 2 Bengkulu Utara students to increase their social sensitivity, (2) If the Jurisprudential Inquiry learning model can be applied to SMA N 2 Bengkulu Utara students to improve student learning achievement, and (3) How the application of the Jurisprudential Inquiry learning model can effectively improve student learning achievement at SMA N 2 Bengkulu Utara. The classroom action research methodology was utilized in this study, followed by a quasi-experiment. Tests of learning achievement and observation were used to obtain data. Descriptive analysis and the t-test were employed in data analysis. Class XI IPS 3 students are the research subjects, and classes XI IPS 1 and XI IPS 2 are the experiment and control classes, respectively. The findings indicated that the adoption of the Jurisprudential Inquiry model could boost student learning achievement and social sensitivity and that it can significantly enhance learning achievement at SMA N 2 Bengkulu Utara.